ALIENASI DAN KRISIS IDENTITAS MANUSIA MODERN: TELAAH ATAS PEMIKIRAN KARL MARX - Losianus Harjon; Ewaldus Nuka; Antonius Redy Yanto Nahak; Theodor Advent Primus Bala Lajar; Ferdinandus Dede; Henokh Albert Ware Mere (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of modernity, characterized by the dominance of global capitalism and digitalization, has triggered identity crises and human alienation. This article aims to examine the phenomenon of the modern human identity crisis through the lens of Karl Marx’s theory of alienation. This crisis manifests in the individual's inability to recognize themselves, the shallowing of social relations, and the reduction of human dignity into mere instruments of production and consumption. Through descriptive qualitative analysis, it is found that alienation in the contemporary era occurs not only in the physical-material dimension but also extends into digital spaces through algorithmic control that obscures self-autonomy. As a solution, it is necessary to restore human existence as creative homo faber and autonomous beings with rational willpower integrity. In conclusion, strengthening critical reflection and authentic relationships is key to overcoming human estrangement amidst the pressures of modern economic structures and technology.